Atomic scale study of silver sulfide leaching with cyanide and thiourea - Bernaola-Flores, R (2019)
This work has been supported by Peru's Consejo Nacional de Ciencia y Tecnologia (CienciActiva - CONCYTEC) and the British Embassy in Lima [contract numbers 154-2015 and 002-2016]. Portions of this research were conducted with the advanced computing resources provided by Texas A&M High Performance Research Computing. Ms. Karinna Visurraga (UTEC) is kindly acknowledged for administrative support.